The Influence of Product Quality on Consumer Loyalty with Customer Satisfaction and Brand Trust as Mediating Variables (Case Research on Samsung Smartphone Consumers in Malang City) - Rohmat; Sudarmiatin; Titis Shinta Dhewi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Indonesian consumers want and demand to get good quality products, have a high awareness of their rights, and always express their interests and fight for their welfare so that the character of these consumers will encourage companies to work more efficiently and innovatively. This research aims to determine the direct and indirect influence of Product Quality on Consumer Loyalty through Customer Satisfaction and Brand Trust among Samsung smartphone consumers. This research uses a descriptive explanatory quantitative approach that describes the relationship between variables and the population of Samsung smartphone consumers in Malang City. The sampling technique using purposive sampling totaled 210 respondents. The research instrument used was a closed questionnaire that had previously been tested, namely through validity and reliability tests so that the questionnaire items were declared valid and reliable to be used as research instruments. Data analysis in this research, includes a) descriptive data analysis, b) classical assumption test, c) path analysis, and finally d) Sobel test. This research uses the SPSS version 25 data processing program. The results show: Directly product quality has a significant effect on consumer loyalty with a significance value of 0.033 and a beta value of 0.165. 2) Directly product quality has a significant effect on customer satisfaction with a significance value of 0.000 and a beta value of 0.501. 3) Directly product quality has a significant effect on brand trust with a significance value of 0.000 and a beta value of 0.780. 4) Directly customer satisfaction has a significant effect on consumer loyalty with a significance value of 0.000 and a beta value of 0.503. 5) Directly brand trust has a significant effect on consumer loyalty with a significance value of 0.021 and a beta value of 0.181. 6) Indirectly product quality has a significant effect on consumer loyalty through customer satisfaction with an indirect influence value of 0.252. 7) Indirectly product quality has a significant effect on consumer loyalty through brand trust with an indirect influence value of 0.141